2014
DOI: 10.3400/avd.oa.14-00067
|View full text |Cite
|
Sign up to set email alerts
|

Strain Analysis of Wall Motion in Abdominal Aortic Aneurysms

Abstract: Objective: In this exploratory study, we used ultrasound speckle-tracking methods, originally used for analyzing cardiac wall motion, to evaluate aortic wall motion. Materials and Methods: We compared 19 abdominal aortic aneurysm (AAA) patients with 10 healthy volunteers (diameter, 48 mm vs. 15 mm). Motion pictures of the axial view of the aneurysm using ultrasonography were analyzed. Circumferential strain and strain rate at 6 equally divided segments of the aorta were semiautomatically calculated. We termed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
4
11
0
1
Order By: Relevance
“…Karatolios et al used 4D ultrasound (US) and speckle‐tracking to quantify linearized strain in healthy and aneurysmal abdominal aortas and described circumferential heterogeneities in both, but did not report regional quantifications of strain . Taniguchi et al also reported heterogeneities in linearized strain between six circumferential regions of the abdominal aorta at the level of the inferior mesenteric artery in 10 healthy volunteers (<40 years) using 2D US speckle‐tracking, but did not report mean regional strain or statistical comparisons between regions . Finally, in a limited study of three patients with AAAs using the relative motion of anatomical markers on cardiac‐gated computed tomography (CT) imaging, Tierney et al noted regional heterogeneities in estimates of linearized strain in the abdominal aorta in cross‐sections both proximal to and within AAAs, but again no regional statistics were provided .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karatolios et al used 4D ultrasound (US) and speckle‐tracking to quantify linearized strain in healthy and aneurysmal abdominal aortas and described circumferential heterogeneities in both, but did not report regional quantifications of strain . Taniguchi et al also reported heterogeneities in linearized strain between six circumferential regions of the abdominal aorta at the level of the inferior mesenteric artery in 10 healthy volunteers (<40 years) using 2D US speckle‐tracking, but did not report mean regional strain or statistical comparisons between regions . Finally, in a limited study of three patients with AAAs using the relative motion of anatomical markers on cardiac‐gated computed tomography (CT) imaging, Tierney et al noted regional heterogeneities in estimates of linearized strain in the abdominal aorta in cross‐sections both proximal to and within AAAs, but again no regional statistics were provided .…”
Section: Discussionmentioning
confidence: 99%
“…31 Taniguchi et al also reported heterogeneities in linearized strain between six circumferential regions of the abdominal aorta at the level of the inferior mesenteric artery in 10 healthy volunteers (<40 years) using 2D US speckle-tracking, but did not report mean regional strain or statistical comparisons between regions. 36 Finally, in a limited study of three patients with AAAs using the relative motion of anatomical markers on cardiac-gated computed tomography (CT) imaging, Tierney et al noted regional heterogeneities in estimates of linearized strain in the abdominal aorta in cross-sections both proximal to and within AAAs, but again no regional statistics were provided. 37 Using DENSE, we present regional quantification and statistical comparison of in vivo heterogeneities in the circumferential strain of the abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
“…A higher relative dispersion of strain is representative of localized heterogeneity of the AAA wall structure, which may ultimately disclose the wall's localized site of highest rupture risk. 28 This underscores the importance of calcification in the assessment of AAA wall motion.…”
Section: Discussionmentioning
confidence: 93%
“…I * , which is an index of viscoelastic deterioration of the vascular wall, is measured by a simple, noninvasive, and feasible technique in clinical settings and is an effective predictor of coronary artery disease, as reported in a clinical paper in 2015. 91) Furthermore, based on chaos theory, a noninvasive diagnostic tool for aneurysm was proposed 17),84), 90) and validated in artificial blood vessels by analysis of aneurysm characteristics, 17), 92) computational fluid dynamics, 93) and clinical measurements. 17),84),90), 94) 6.…”
Section: A Noninvasive Diagnostic Methods For Blood Vessel Diseasementioning
confidence: 99%